2008
DOI: 10.1166/jnn.2008.163
|View full text |Cite
|
Sign up to set email alerts
|

Stacking Faults in SiC Nanowires

Abstract: SiC nanowires were obtained by a reaction between vapor silicon and multiwall carbon nanotubes, CNT, in vacuum at 1200 degrees C. Raman and IR spectrometry, X-ray diffraction and high resolution transmission electron microscopy, HRTEM, were used to characterize properties of SiC nanowires. Morphology and chemical composition of the nanowires was similar for all samples, but concentration of structural defects varied and depended on the origin of CNT. Stacking faults were characterized by HRTEM and Raman spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…The space between two planes in Figure was about 0.25 nm which is concurrent with the calculated value in the 3C-SiC structure (0.251 nm). The stacking faults confirmed that the nanowires were grown by stacking the (111) lattice plane in the [111] direction. …”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The space between two planes in Figure was about 0.25 nm which is concurrent with the calculated value in the 3C-SiC structure (0.251 nm). The stacking faults confirmed that the nanowires were grown by stacking the (111) lattice plane in the [111] direction. …”
Section: Resultsmentioning
confidence: 70%
“…The stacking faults confirmed that the nanowires were grown by stacking the (111) lattice plane in the [111] direction. [15][16][17] 3.4. Discussion on Different Binding Mechanisms.…”
Section: After Pyrolysismentioning
confidence: 99%
“…Synthesis of SiC NWs predominantly relies on the vapor-liquid-solid (VLS) growth mode. The list of reported synthesis techniques includes reaction of carbonsource gases with Si substrates, 5 pyrolysis of powders containing the source materials, [6][7][8] reaction of source gases with carbon nanotubes, 9,10 microwave heating-assisted physical vapor transport, 11 and chemical vapor deposition (CVD). [12][13][14] Various substrates have been used for SiC NW synthesis, including SiO 2 , [14][15][16] graphite, 6,8,17,18 poly-SiC, 12 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2E shows XRD patterns of the SiC NWs. The peaks at 36°, 41°, 60°, and 72° correspond to the (1 1 1), (2 0 0), (2 2 0), and (3 1 1) reflections of β‐SiC, and the peak at 33° is caused by stacking faults in β‐SiC 40,41 . After oxidation at 900°C, broad peak at 22° appeared, indicating the formation of amorphous SiO 2 oxide scale 40 .…”
Section: Resultsmentioning
confidence: 99%